Safety of concomitant administration of inactivated hepatitis A vaccine with other vaccines in children under 16 years old in post-marketing surveillance. Issue 14 (31st March 2023) - Wu, Linlin; Yang, Shoufei; Huang, Zhuoying; Liu, Jiechen; Guo, Xiang; Bai, Qingrui; Sun, Xiaodong
Abstract: Background: Concomitant administration refers to the receipt of two or more vaccines during a single healthcare encounter, which is an efficient way to increase vaccination coverage in children. However, the post-marketing safety studies of concomitant administration are scarce. Inactivated hepatitis A vaccine (Healive®) has been used widely in China and other countries for more than a decade. We aimed to explore the safety of Healive® co-administered with other vaccines compared to Healive® alone in children under 16 years old. Methods: We retrieved Adverse Events Following Immunization (AEFI) cases and vaccination doses of Healive® during 2020–2021 in Shanghai, China. The AEFI cases were divided into concomitant administration group and Healive® alone group. We used administrative data on vaccine doses as denominators to calculate and compare crude reporting rates between groups. We also compared baseline gender and age distribution, clinical diagnoses, and time interval from vaccination to onset of symptoms between groups. Results: A total 319, 247 doses of inactivated hepatitis A vaccine (Healive®) were used and 1, 020 AEFI cases (319.50 per million doses) associated with Healive® were reported during 2020–2021 in Shanghai. There were 259, 346 doses concomitantly administered with other vaccines and 830 AEFI cases (320.04 per million doses) were reported. There were 59, 901 doses of Healive® that vaccinated alone, with 190 AEFI cases (317.19 per million doses). There was only one case with serious AEFI in concomitant administration group, with a rate of 0.39 per million doses. Reported rates of AEFI cases were similar between groups in general (p > 0.05). Conclusion: Concomitant administration of inactivated hepatitis A vaccine (Healive®) with other vaccines has a similar safe profile as Healive® alone.